2014
DOI: 10.1890/es14-00230.1
|View full text |Cite
|
Sign up to set email alerts
|

Modeling and mapping isotopic patterns in the Northwest Atlantic derived from loggerhead sea turtles

Abstract: Abstract. Stable isotope analysis can be used to infer geospatial linkages of highly migratory species.Identifying foraging grounds of marine organisms from their isotopic signatures is becoming de rigueur as it has been with terrestrial organisms. Sea turtles are being increasingly studied using a combination of satellite telemetry and stable isotope analysis; these studies along with those from other charismatic, highly vagile, and widely distributed species (e.g., tuna, billfish, sharks, dolphins, whales) h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
43
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 52 publications
(47 citation statements)
references
References 81 publications
4
43
0
Order By: Relevance
“…The variability observed in the current study is perhaps not surprising, as freshwater turtle population studies have revealed sex-specific, temporally varying growth patterns and maturation schedules, in addition to differences between geographically adjacent populations that diverge only somewhat in habitat and forage type (Gibbons 1967;Gibbons et al 1981;Frazer et al 1991a, b;Snover et al 2015). In comparison, movements and habitat use for the loggerhead sea turtle population considered in the current study encompass much of the North Atlantic Ocean basin (Bolten 2003;Ceriani et al 2014). Within this large region, dichotomies in migration and foraging strategies have been observed for both juveniles (McClellan and Read 2007;Mansfield et al 2009) and adults (Reich et al 2009) and individuals appear to exhibit a degree of consistency in resource use at different life stages (Avens et al 2003;McClellan et al 2010;Vander Zanden et al 2010).…”
Section: Discussionmentioning
confidence: 51%
See 1 more Smart Citation
“…The variability observed in the current study is perhaps not surprising, as freshwater turtle population studies have revealed sex-specific, temporally varying growth patterns and maturation schedules, in addition to differences between geographically adjacent populations that diverge only somewhat in habitat and forage type (Gibbons 1967;Gibbons et al 1981;Frazer et al 1991a, b;Snover et al 2015). In comparison, movements and habitat use for the loggerhead sea turtle population considered in the current study encompass much of the North Atlantic Ocean basin (Bolten 2003;Ceriani et al 2014). Within this large region, dichotomies in migration and foraging strategies have been observed for both juveniles (McClellan and Read 2007;Mansfield et al 2009) and adults (Reich et al 2009) and individuals appear to exhibit a degree of consistency in resource use at different life stages (Avens et al 2003;McClellan et al 2010;Vander Zanden et al 2010).…”
Section: Discussionmentioning
confidence: 51%
“…Episodic increases in bottom water temperature in the Mid-Atlantic Bight (MAB) during the time period from 1958 to 2007 were recently found to correspond with significantly reduced growth and increased mortality for the surfclam (Spisula solidissima) population, particularly on the inner shelf (Narváez et al 2015). Given that the MAB provides important foraging habitat for large neritic juvenile and adult loggerhead sea turtles (Arendt et al 2012;Griffin et al 2013;Ceriani et al 2014), the potential for linkages between temperature changes, benthic productivity, and loggerhead growth dynamics merits further investigation.…”
Section: Growthmentioning
confidence: 99%
“…The isotopic data generated in this study adds to the growing body of work describing stable isotope baseline data for marine organisms in the eastern Pacific Ocean (Arthur et al, 2008;Olson et al, 2010;Ruiz-Cooley and Gerrodette, 2012;. A natural future direction would be to estimate marine isoscapes across taxa and trophic levels to provide a systematic framework for stable isotope ecological applications, as well as empirical studies of trophic dynamics (Somes et al, 2010;Ceriani et al, 2014;Vander Zanden et al, 2015;Magozzi et al, 2017;Kurle and McWhorter, 2017). A central repository of stable isotope data for sea turtles would support the advancement of this field and reduce duplication of efforts (Pauli, 2017).…”
Section: Discussionmentioning
confidence: 96%
“…Thus, stable isotope ratios function as intrinsic markers that reflect the isotopic composition of the environment (location and food web) where the tissues were synthesized (Hobson and Norris 2008). Because geographic variation in stable isotope ratios in marine systems has been described only at very coarse scales (e.g., McMahon et al 2013), isotopic approaches have been validated with telemetry in several marine species such as sea birds (Jaeger et al 2010;González-Solís et al 2011) and sea turtles (e.g., Ceriani et al 2012Ceriani et al , 2014bPajuelo et al 2012b;Seminoff et al 2012).…”
Section: Introductionmentioning
confidence: 99%